Correction of Characteristics of Transverse Vibration Subsystems of Complex Mechanical or/and Mechatronic Systems - Buchacz, Andrzej (Solid state phenomena, 2016)
In this paper the application of analysis within transverse vibrating subsystem of complex or/and mechatronic systems by means of the exact and approximate methods were the main purposes of work. The second purpose - of the work was to solve the task of assignment of frequency-modal analysis within characteristics of mechatronic system. Classical and unclassical methods to solve this problem have been used to obtain the dynamical characteristics in the Gliwice research Centre. During the analysis of the diagrams of characteristics of confirmed system it has been determined that in case of approximate method the resonance frequencies cover with those which have been determined with exact method. However, the values of the characteristic in other areas are different. The main aim of this paper was to compare the transients of characteristics of mechanical subsystem within the transverse vibrating discrete – continuous mechatronic system, obtained by exact and approximate, that means Galerkins method and to answer to the question – if the method can be used to nominate the characteristics of mechatronic systems. The main subject of deliberation was to determine the flexibility of the mechanical system with constant cross section using the exact and Galerkin’s method. The problems presented in this paper, such as the analysis of subsystem of mechatronic and mechanical complex systems is however the introduction to the synthesis of transverse vibrating mechatronic systems with assumed frequency spectrum.